Influence of COVID-19 on postoperative prognosis and pain management - Yue-Zi Hu; Zai-Long Qin; Wen Tang; Zhao-Lan Hu; Ru-Yi Luo (PLoS ONE, 2026)
Background The COVID-19 pandemic has significantly affected healthcare, particularly surgical care. Although short-term effects on surgical outcomes have been examined, understanding of long-term postoperative prognosis and pain management in COVID-19 patients remains limited. This knowledge gap is critical as the pandemic evolves and the need for optimized postoperative care becomes increasingly important. Objective The primary objective of this study was to evaluate the impact of COVID-19 infection on postoperative outcomes and pain management in surgical patients. We aimed to assess surgical mortality, complication rates, and postoperative pain levels in COVID-19-positive patients relative to a closely matched control group. Methods We conducted a retrospective cohort study of COVID-19 patients admitted to the ICU following surgery. Data were collected on baseline characteristics, postoperative complications, mortality and pain scores. Univariate and multivariate linear regression models were used to evaluate the impact of COVID-19 infection on postoperative pain. Stratified and interaction analyses were additionally performed to examine the robustness of these associations across subgroups. Results Mortality rates and the incidence of sepsis were significantly higher in the COVID-19 cohort. Patients with COVID-19 also experienced longer duration of mechanical ventilation in the ICU and prolonged ICU stays. In the fully adjusted multivariate linear regression model, COVID-19 infection was positively associated with higher postoperative visual analog scale pain scores (β = 1.51; 95% CI: 1.03–1.98; p < 0.001), corresponding to an average increase of 1.51 units in postoperative pain. Stratified analysis largely corroborated these findings across subgroups. Conclusions Surgical intervention in patients with COVID-19 was associated with higher mortality and sepsis rates, longer ICU stays, and increased postoperative pain scores. These findings highlight the need for continued research to optimize surgical care and improve patient outcomes in the evolving post-pandemic era.